Microbiota-gut-brain-axis: a new target of acupuncture therapy for post-stroke cognitive impairment - Ba, Te; Niu, Rui; Gao, Jianjun; Li, Wenfang; Dong, Mengwei; Duan, Jingjing; Gong, Yinan; Wu, Sinuo; Lyu, Zhongxi; Liu, Yang; Li, Ningcen (Frontiers in Microbiology, 2025)
Stroke-induced cognitive impairment is a common complication and an important risk factor for disability. Prevention and treatment of secondary stroke injuries are crucial. Modern research has found that the gut microenvironment can directly or indirectly affect neurological function and cerebral ischemic outcomes, and their crosstalk is achieved through the microbiota-gut-brain-axis (MGBA). Acupuncture, as a promising non-drug treatment, has been recommended for improving post-stroke cognitive impairment (PSCI). However, in recent years, few studies have systematically analyzed the potential mechanisms in this field, and whether acupuncture can improve PSCI through the MGBA remains to be explored. This review comprehensively summarizes literature and shows that, acupuncture, as an adjuvant therapy can play a potential important role in the treatment of PSCI by regulating the microbiota-gut-brain-axis. Acupuncture can repair intestinal epithelial barrier, regulate gut microbiota and serum metabolites, alleviate gut inflammation and neuroinflammation, and regulating HPA axis function, etc. From the studies we have included, the evidence for its effectiveness remains limited, these results should be interpreted with caution due to the low quality of evidence. Future high-quality clinical and experimental studies are needed. This review also discussed the development prospects of acupuncture in improving PSCI via the MGBA, such as genomics, personalized therapy, establishment of standards, and combination therapy, etc. providing new research ideas and scientific and reliable evidence for the application of acupuncture in PSCI.